2D organic molecular metallic soft material derived from BEDO-TTF with electrochromic and rectifying properties. (December 2018) - Suarez, Daniel; Steven, Eden; Laukhina, Elena; Gomez, Andres; Crespi, Anna; Mestres, Narcis; Rovira, Concepció; Choi, Eun; Veciana, Jaume
Abstract In this article we demonstrate that a migration of iodine species and chemical transformation in a moist environment induced by a voltage-biased Pt electrode is able to alter the color and degree of charge transfer in a layer of the 2D organic molecular metal (BEDO-TTF)2.4 I3 [BEDO = bis(ethylenedioxy)tetrathiafulvalene] self-assembled at the surface of a polycarbonate film. These effects produce a reversible electrochromic behavior of the layer with low operating voltages and fast operation times. Adjuvant with electrochromism, this flexible material exhibits rectifying behavior whose I-V curves are dependent on the voltage sweep directions. These results open new possibilities for the design and fabrication of organic flexible materials for soft electrochromic and rectifying components. The easy working principle ensures reliability, low power consumption, and versatility through its implementation into simple devices. Such working principle has been confirmed by temperature dependent resistance measurements, X-Ray, EDX-SEM, and conducting-AFM studies. Molecular metal: dual functional devices enabled Migration and chemical transformation of iodine species in the organic salt has been utilized to make dual functional devices that can operate at low voltages. An international team led by Dr. Eden Steven from Florida State University, USA and Elena Laukhina from Ciber-BBN (ICMAB-CSIC), Spain develops flexible electrochromic and rectifying components based on bi-layered thin films of a molecular metal. The thin film consists of a thin polycarbonate substrate and a metallic triiodide salt of an organic molecule BEDO-TTF which undergoes losses or restore of I3- anions under forward or reverse biases in the presence of water, respectively, resulting in discoloration/coloration and electrical rectifying behavior. The simple working principle and the versatile functionalities shown here enable promising design and fabrication of organic electrochromic and rectifying devices in the near future.